2022
DOI: 10.1097/gox.0000000000004115
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electrical Stimulation in Peripheral Nerve Regeneration: A Systematic Review

Abstract: Background: Functional recovery after peripheral nerve injury is often suboptimal despite the intrinsic permissive growth environment of the peripheral nervous system. The objective of this systematic review is to explore the use of electrical stimulation (ES) for peripheral nerve regeneration. Methods: A systematic literature search was conducted from inception to March 2, 2021 to retrieve articles on ES for peripheral nerve regeneration using the PubMed, Ovid MEDLINE, and Embase databases. Primary outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…One of the most important observations we made when comparing these studies to one another was the high variation in electrical stimulation protocols with regard to frequency, duration, stimulation onset or conduit type. This was also noticed by ElAbd et al [ 44 ] in 2022. Since ES + NGC treatment is a rather new approach, no standardized guidelines have been established so far.…”
Section: Discussionsupporting
confidence: 80%
“…One of the most important observations we made when comparing these studies to one another was the high variation in electrical stimulation protocols with regard to frequency, duration, stimulation onset or conduit type. This was also noticed by ElAbd et al [ 44 ] in 2022. Since ES + NGC treatment is a rather new approach, no standardized guidelines have been established so far.…”
Section: Discussionsupporting
confidence: 80%
“…However, there may be a role for this approach after muscle reinnervation has occurred to increase muscle strength as an adjunct to sensory re-education. Low-frequency repetitive nerve stimulation is a more promising technique and has been shown to stimulate rapid motor reinnervation postoperatively [76–78,79 ▪ ,80,81 ▪ ]. Optimization of stimulation settings and evaluation of this technique in specific clinical scenarios is still required [76,82].…”
Section: Managementmentioning
confidence: 99%
“…The diagnostic basis for neuromodulation is the same for surgical interventions and includes an electrophysiological examination of motor nerve conduction and the physical symptoms supporting nerve injury (e.g., numbness, weakness). Specifically, there is some evidence that PNS/electrical stimulation (ES) is effective [ 26 , 27 ]. Jo et al demonstrated in a comparative study on mice that ES is equally as efficacious as FK506 (Tacrolimus) treatment [ 28 ].…”
Section: Introductionmentioning
confidence: 99%